Sex reversal and early larval biology of farmed silver perch, Bidyanus bidyanus (Mitchell, 1838) in Western Australia (Curtin University, 2017)
The intensive aquaculture of silver perch in Western Australia is constrained by the lack of control on the broodstock sex and a detailed biological information on the early larval stages. Five experiments were performed to study the reproductive biology of the species, the sex reversals and the feeding biology of the early life of larvae. The result showed that the domestication of the broodstock and the sex reversal are viable options with hormonal feed supplementations.